Laparoscopic versus ultrasound-guided transversus abdominis plane block for postoperative pain management in minimally invasive colorectal surgery: a meta-analysis protocol - Yang, Wenming; Yuan, Tao; Cai, Zhaolun; Ma, Qin; Liu, Xueting; Zhou, Hang; Qiu, Siyuan; Yang, Lie (Frontiers in Oncology, 2023)
Introduction: Transversus abdominis plane block (TAPB) is now commonly administered for postoperative pain control and reduced opioid consumption in patients undergoing major colorectal surgeries, such as colorectal cancer, diverticular disease, and inflammatory bowel disease resection. However, there remain several controversies about the effectiveness and safety of laparoscopic TAPB compared to ultrasound-guided TAPB. Therefore, the aim of this study is to integrate both direct and indirect comparisons to identify a more effective and safer TAPB approach. Materials and methods: Systematic electronic literature surveillance will be performed in the PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov databases for eligible studies through July 31, 2023. The Cochrane Risk of Bias version 2 (RoB 2) and Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tools will be applied to scrutinize the methodological quality of the selected studies. The primary outcomes will include (1) opioid consumption at 24 hours postoperatively and (2) pain scores at 24 hours postoperatively both at rest and at coughing and movement according to the numerical rating scale (NRS). Additionally, the probability of TAPB-related adverse events, overall postoperative 30-day complications, postoperative 30-day ileus, postoperative 30-day surgical site infection, postoperative 7-day nausea and vomiting, and length of stay will be analyzed as secondary outcome measures. The findings will be assessed for robustness through subgroup analyses and sensitivity analyses. Data analyses will be performed using RevMan 5.4.1 and Stata 17.0. P value of less than 0.05 will be defined as statistically significant. The certainty of evidence will be examined via the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) working group approach. Ethics and dissemination: Owing to the nature of the secondary analysis of existing data, no ethical approval will be required. Our meta-analysis will summarize all the available evidence for the effectiveness and safety of TAPB approaches for minimally invasive colorectal surgery. High-quality peer-reviewed publications and presentations at international conferences will facilitate disseminating the results of this study, which are expected to inform future clinical trials and help anesthesiologists and surgeons determine the optimal tailored clinical practice for perioperative pain management. Registration number: PROSPERO CRD42021281720.